2022
DOI: 10.3390/molecules27196692
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Oxygen Management during the Post-Fermentation Stage on Acetaldehyde, Color, and Phenolics of Vitis vinifera L. Cv. Cabernet Sauvignon Wine

Abstract: Oxygen exposure is unavoidable and the impact of its management during the post-fermentation stage (PFS) on dry red wine is poorly investigated. This study was dedicated to the variation of acetaldehyde, color and phenolics of Cabernet Sauvignon dry red wine during five discontinuous oxidation cycles of four levels of controlled oxygen supply, which were carried out to simulate probable oxidation during the PFS. Free SO2 disappeared after the first, second and third oxidation cycles in wines with high, medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…A study of Cabernet Sauvignon wines during post‐fermentation stage found that the acetaldehyde content of high‐level oxygenation wines (3‐3.9 mg O 2 /L per time) increased from 4 to 11 mg/L. The acetaldehyde content of wines with low levels of oxidation did not change much (from 4 to 5 mg/L) (Dai, Sun, et al., 2022). The influence of varying acetaldehyde levels (4.86 ± 0.60, 8.67 ± 1.14, and 29.66 ± 1.74 mg/L) on the aging dynamics of Cabernet Sauvignon wines was studied over a 12‐month period.…”
Section: Oxygen (O2)mentioning
confidence: 99%
“…A study of Cabernet Sauvignon wines during post‐fermentation stage found that the acetaldehyde content of high‐level oxygenation wines (3‐3.9 mg O 2 /L per time) increased from 4 to 11 mg/L. The acetaldehyde content of wines with low levels of oxidation did not change much (from 4 to 5 mg/L) (Dai, Sun, et al., 2022). The influence of varying acetaldehyde levels (4.86 ± 0.60, 8.67 ± 1.14, and 29.66 ± 1.74 mg/L) on the aging dynamics of Cabernet Sauvignon wines was studied over a 12‐month period.…”
Section: Oxygen (O2)mentioning
confidence: 99%
“…Temperature With the fermentation temperature adjusted from 16 to 24 • C, the acetaldehyde content is decreased from 19 to 13 mg/L 31.58% [12] Ventilation The acetaldehyde content is decreased from 10.92 to 4.21 mg/L in low-level oxygenation compared with high-level oxygenation 61.45% [13] SO 2…”
Section: Effect Efficiency Referencementioning
confidence: 99%